Bioengineered Rat Kidney Tissue Model for Drug Toxicity Assessment - Parisi, Erika Joy (Tufts Archival Research Center, 2005)
Nephrotoxicity is induced by a variety of marketed pharmaceuticals, and kidney toxicity is one of the main reasons for failure in preclinical safety trials. The launch of a novel drug on the market has proven an extremely time-consuming and expensive endeavor; therefore, innovative pre-clinical assessment methods are urgently required in order to better screen for more promising candidates. The development of a novel technique for the construction of a sustainable 3D rat kidney model upon which to evaluate the nephrotoxic effects of select pharmaceuticals is reported. Normal rat kidney epithelial and fibroblast cells were cultured in extracellular matrix molecules in order to develop the organ model. The results supported co-culturing with fibroblasts and indicated the collagen-matrigel mixture mediated optimal morphogenesis for both cell types. Structural features of the tubule-like formations of the kidney tissue were validated based on the distribution of GGT-1, Aquaporin 2, and Cytokeratin 8,18,19. Additionally, MTT and LDH cytotoxicity assays demonstrated a severe effect on the NRK52E and 49F cells, especially at 10 uM and 100 uM concentrations.